Novas arquiteturas para sensores modificados com materiais nanoestruturados de carbono - Baccarin, Marina (Universidade Federal de São Carlos, 2016)
In this work are reported the development of new architectures for sensors using carbon nanomaterials. Firstly, the investigation of the nanomaterials reduced graphene oxide (RGO) and carbon black (CB) in chitosan film (CTS) modifying the surface of a glassy carbon electrode (GCE) for the development of new electrochemical sensor is described. The sensor was characterized by using scanning electron microscopy (SEM), ultraviolet spectroscopy, Fourier transform infrared spectroscopy, dynamic light scattering and cyclic voltammetry (CV). Using the Nicholson method and the results obtained by CV with the proposed RGO-CB-CTS/GCE, the heterogeneous electron transfer rate constant (k0) of 5.6 × 10−3 cm s−1 was obtained. The proposed electrode was applied for the simultaneous determination of dopamine (DA) (neurotransmitter) and paracetamol (PAR) (analgesic). Employing SWV, DA presented an anodic peak at 0.25 V and PAR at 0.50 V vs. Ag/AgCl (3.0 mol L–1 KCl). The analytical curves obtained were linear in the range from 3.9  10–6 to 3.4  10–5 mol L–1 and between 2.0  10–6 and 1.7  10–5 mol L–1 with detection limits of 2.0  10–8 and 5.3  10–8 mol L–1 for DA and PAR, respectively. The developed sensor presented advantages such as simple preparation, low cost of nanomaterials used, fast response (7 s for each measure). Besides, the sensor was successfully applied in the simultaneous determination of the analytes in synthetic urine samples. The second fabricated sensor was based on the modification of a GCE with nanodiamond (Dnano) within a Poly(allylamine hydrochloride) (PAH) film. The Dnano-PAH/GCE sensor was characterized by Fourier transform infrared spectroscopy and cyclic voltammetry. It was observed a stability of the dispersion and a k0 of 2.0 × 10−2 cm s−1 was obtained using the Nicholson method and the results obtained from CV technique. The developed sensor was applied for determination of catechol (CAT) using differential-pulse Baccarin, M. ix voltammetry (DPV). Under optimal experimental conditions, the anodic peak current was linear in the CAT concentration range of 2.0 × 10−6 to 1.1 × 10−4 mol L−1 with a detection limit of 1.5 × 10−6 mol L−1. The proposed method was applied for the determination of CAT in natural water samples, presenting vantages such as fast response (9 s to carry out one measure), selectivity and simplicity of working electrode fabrication.
New architectures for sensors using carbon nanomaterials
Keywords: Sensores; Materiais; Carbono; Nanoestruturados; CIENCIAS EXATAS E DA TERRA::QUIMICA